نظرة شرعية في المقاطعة الاقتصادية لنصرة خير البريّة صلى الله عليه وسلم - سليمان, بن صفية (جامعة الوادي university of eloued, 2023)
من وسائل الدفاع عن النبي صلى الله عليه وسلم المقاطعة الاقتصادية، فما حكمها؟ وما ضوابطها؟. والهدف من الدراسة بيان الموقف الشرعي من المقاطعة الاقتصادية. ولتحقيق ذلك استخدمت المنهجين التحليلي والمقارن. وكان من نتائج هذه الدراسة: جواز المقاطعة الاقتصادية لنصرة النبي صلى الله عليه وسلم، إذا لم يترتب عليها ضرر أكبر. Abstract : One of the means of defending the Prophet, may God bless him and grant him peace, is the economic boycott. What is the ruling on it? And what are its controls? The aim of the study is to clarify the legitimate position on the economic boycott. To achieve this, the analytical and comparative approaches were used. One of the results of this study: the permissibility of the economic boycott to support the Prophet, may God’s prayers and peace be upon him, if it does not result in greater harm. Keywords: economic boycott, Nusra, the Prophet, may God bless him and grant him peace
مقال
Keywords: المقاطعة ; الاقتصادية ; النصرة